2006
DOI: 10.1186/1472-6823-6-4
|View full text |Cite
|
Sign up to set email alerts
|

Insulin versus oral agents in the management of Cystic Fibrosis Related Diabetes: a case based study

Abstract: BackgroundInsulin is the recommend therapeutic agent of choice for the management of Cystic Fibrosis Related Diabetes (CFRD), despite only sub-optimal reductions in glycemic control and increased morbidity and mortality reported by centers using this agent. The newer insulin sensitizing agents demonstrated to have anti-inflammatory mechanisms may provide an alternative management option for CFRD.MethodsA prospective case based therapeutic comparison between insulin, sulfonylurea, metformin and thiazolidinedion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
2

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 20 publications
(16 reference statements)
0
17
0
2
Order By: Relevance
“…While CFRD is traditionally believed to be caused by insulinopenia due to pancreatic b cell fibrosis, recent studies have suggested that impaired insulin sensitivity contributes to CFRD and that insulin resistance frequently develops during infections (37,43). Small observational studies of patients with CFRD have demonstrated that metformin is not associated with adverse events such as hypoglycemia or lactic acidosis (37). Furthermore, the efficacy of metformin was comparable to that of insulin, in regard to HbA 1C reduction and weight gain.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…While CFRD is traditionally believed to be caused by insulinopenia due to pancreatic b cell fibrosis, recent studies have suggested that impaired insulin sensitivity contributes to CFRD and that insulin resistance frequently develops during infections (37,43). Small observational studies of patients with CFRD have demonstrated that metformin is not associated with adverse events such as hypoglycemia or lactic acidosis (37). Furthermore, the efficacy of metformin was comparable to that of insulin, in regard to HbA 1C reduction and weight gain.…”
Section: Discussionmentioning
confidence: 92%
“…The incidence of CFrelated diabetes mellitus (CFRD) has been increasing with the increased lifespan of individuals with CF, currently occurring in approximately 30% of adult patients with CF as per the CF patient registry. While CFRD is traditionally believed to be caused by insulinopenia due to pancreatic b cell fibrosis, recent studies have suggested that impaired insulin sensitivity contributes to CFRD and that insulin resistance frequently develops during infections (37,43). Small observational studies of patients with CFRD have demonstrated that metformin is not associated with adverse events such as hypoglycemia or lactic acidosis (37).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Apesar das poucas evidências clínicas, existem pacientes que são controlados com antidiabéticos orais secretagogos de insulina, como glinidas (repaglinida) (47) e sulfoniluréias (glibenclamida) (48,49), enquanto a relação risco-benefício é ainda incerta para a utilização de agentes sensibilizantes da ação insulínica, como a metformina e as tiazolidinedionas (49). A acarbose, um inibidor da enzima alfa-glicosidase, apesar de reduzir a glicemia pós-prandial, causa diarréia, anorexia e desconforto abdominal, não sendo indicada para pacientes desnutridos (16,41).…”
Section: Diabetes Relacionado à Fibrose Císticaunclassified
“…Orale Antidiabetika werden in der Praxis zwar nicht selten "offlabel" den Patienten rezeptiert, sind aber bisher nicht hinreichend bezüglich Wirksamkeit und Sicherheit bei CFRD untersucht. Einzelne Berichte deuten aber einen möglichen Einsatz bei früh diagnostiziertem CFRD an [16]. Sie können aus diesem Grund nur innerhalb von kontrollierten Studien, die aktuell noch laufen, eingesetzt werden.…”
Section: Introductionunclassified